2012
DOI: 10.1111/j.1460-9592.2012.03861.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance characteristics and efficiency of suprazygomatic maxillary nerve blocks in infants: a descriptive prospective study

Abstract: With a very low technical failure rate and a good clinical success rate, ultrasound appears to be a useful and simple tool to aid suprazygomatic maxillary nerve block in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 13 publications
3
45
0
Order By: Relevance
“…A case series of ultrasound-guided suprazygomatic maxillary nerve blocks for cleft palate repair in children concluded that ultrasound allows good visualization of local anesthetic spread (spread seen in 94% of cases). 24 Palmer et al 17 prospectively audited the use of ultrasound-guided TAP block and found no significant correlation between dermatomal block spread and dose, volume, or concentration, although this study was limited by a small sample size.…”
Section: B (Sufficient Postoperative Analgesia)mentioning
confidence: 80%
See 1 more Smart Citation
“…A case series of ultrasound-guided suprazygomatic maxillary nerve blocks for cleft palate repair in children concluded that ultrasound allows good visualization of local anesthetic spread (spread seen in 94% of cases). 24 Palmer et al 17 prospectively audited the use of ultrasound-guided TAP block and found no significant correlation between dermatomal block spread and dose, volume, or concentration, although this study was limited by a small sample size.…”
Section: B (Sufficient Postoperative Analgesia)mentioning
confidence: 80%
“…There were 23 and 13 articles reporting quality and outcomes of ultrasound imaging for the pediatric population in peripheral and neuraxial blockade, respectively ( Table 2). From the peripheral nerve block (PNB) set, there were 10 RCTs, 4-13 6 prospective observational studies, [14][15][16][17][18][19] 2 retrospective studies, 20,21 and 5 case series [22][23][24][25][26] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to head and neck blocks, the use of ultrasound images has been implicated in various superficial to deep nerve blocks. [7][8][9] Although trigeminal nerve blockade via the pterygopalatine fossa (PPF) under ultrasound guidance has been described in several reports, [10][11][12][13] the key anatomical landmarks, including the maxilla and lateral pterygoid plate (LPP), on ultrasound imaging remain unclear.…”
mentioning
confidence: 99%
“…The effectiveness of bilateral maxillary nerve blocks using a suprazygomatic approach with nerve stimulation [ 19 ] and ultrasound [ 21 ] has been reported. Using electrical stimulation, Mesnil et al [ 19 ] showed that the disappearance of the temporal muscle twitch coincided with the needle's tip in the pterygopalatine fossa where local anesthetic was injected.…”
Section: Current Literature In Ultrasoundguided Approachesmentioning
confidence: 99%
“…Using electrical stimulation, Mesnil et al [ 19 ] showed that the disappearance of the temporal muscle twitch coincided with the needle's tip in the pterygopalatine fossa where local anesthetic was injected. More recently, this group successfully published a randomized, double-blind study evaluating an ultrasound-guided suprazygomatic maxillary nerve block [ 21 ]. They used a linear array probe located in the infrazygomatic area to allow out-of-plane visualization of the needle tip and local anesthetic spread in the pterygopalatine fossa.…”
Section: Current Literature In Ultrasoundguided Approachesmentioning
confidence: 99%